Childhood trauma and sex addiction among adult men - Giordano, Amanda L. (Journal of addictions & offender counseling, 2024)
This study explored the relationship between childhood trauma and sex addiction among a sample of adult men (N = 149). Thirty-eight (25.5%) men screened positive for sex addiction, whereas 111 (74.5%) did not. Using descriptive discriminant analysis, we found that four subscales of early trauma predicted risk of sex addiction group membership to varying degrees, accounting for 22.3% of the variance explained. Sexual and emotional abuse accounted for the most variance explained in the group differences, whereas physical abuse and, to a lesser extent, general trauma also contributed to the group differences. Implications of the study findings are discussed.